1992
DOI: 10.1055/s-0038-1656308
|View full text |Cite
|
Sign up to set email alerts
|

Thromboembolic Disease – Critical Evaluation of Laboratory Investigation

Abstract: SummaryPrevious studies of patients with thromboembolic disease have revealed an association either with hereditary anticoagulant protein deficiencies or with defects in the fibrinolytic system. To obtain a more comprehensive picture and to investigate which analyses are useful in the evaluation of such patients, we have performed an extensive laboratory investigation in 439 individuals with thromboembolic disease. Anticoagulant protein deficiencies were found in 24 patients. Deficiencies of protein C (n = 10)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
51
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(55 citation statements)
references
References 48 publications
4
51
0
Order By: Relevance
“…Our study demonstrated the FV : R506Q mutation to be an important risk factor in outpatients with DVT. This is in marked contrast to other congenital prothrombotic disorders, which are only rarely found in thrombosis patients [19][20][21][22][23][24]. More than a quarter of the outpatients with venous thrombosis verified by phlebography were found to be carriers of the FV : R506Q mutation, a strikingly high proportion, even larger than figures reported for selected series of thrombosis patients from other countries [2,4,9,12].…”
Section: Discussionmentioning
confidence: 71%
“…Our study demonstrated the FV : R506Q mutation to be an important risk factor in outpatients with DVT. This is in marked contrast to other congenital prothrombotic disorders, which are only rarely found in thrombosis patients [19][20][21][22][23][24]. More than a quarter of the outpatients with venous thrombosis verified by phlebography were found to be carriers of the FV : R506Q mutation, a strikingly high proportion, even larger than figures reported for selected series of thrombosis patients from other countries [2,4,9,12].…”
Section: Discussionmentioning
confidence: 71%
“…Immunological assays were then designed and used to investigate individuals with thromboembolic disease, as deficiencies of these proteins would hypothetically lead to a thrombotic tendency. The association between thromboembolic disease and deficiency of proteins C or S is now well established (1,3,4). The now hypothesized cofactor to APC is the first anticoagulant factor to be proposed on the basis of observations made in an individual patient with thromboembolic disease.…”
Section: Discussionmentioning
confidence: 99%
“…However, heterozygous deficiencies of anticoagulant proteins can only be found in a minority of cases (4). This suggests that there are genetic defects predisposing for thrombosis yet to be identified.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of protein S deficiency is not quite clear, but is considered to be that of protein C, 1:200. Earlier investigations on the prevalence of deficiencies in the anticoagulant proteins in patients with thrombotic disease, have shown that 4-6% of the patients show such deficiencies (Taberno et al 1991;Malm et al 1992). In our investigation, 11% of the patients showed deficiencies in the anticoagulant proteins.…”
Section: Discussionmentioning
confidence: 99%